2018
DOI: 10.1590/0074-027601700125
|View full text |Cite
|
Sign up to set email alerts
|

Towards a standard protocol for antimony intralesional infiltration technique for cutaneous leishmaniasis treatment

Abstract: BACKGROUNDDespite its recognised toxicity, antimonial therapy continues to be the first-line drug for cutaneous leishmaniasis (CL) treatment. Intralesional administration of meglumine antimoniate (MA) represents an alternative that could reduce the systemic absorption of the drug and its side effects.OBJECTIVESThis study aims to validate the standard operational procedure (SOP) for the intralesional infiltration of MA for CL therapy as the first step before the assessment of efficacy and safety related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Some studies showed that lesions located on the lower limbs needed more time to heal, and venous stasis may be a delaying factor ( Schubach et al, 2005 ; Silva et al, 2018 ). Although the rate of lower limb lesions was not different between groups, patients in the IL-MA group with lesions on the lower limbs had a lower rate of cure than patients with upper limbs lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that lesions located on the lower limbs needed more time to heal, and venous stasis may be a delaying factor ( Schubach et al, 2005 ; Silva et al, 2018 ). Although the rate of lower limb lesions was not different between groups, patients in the IL-MA group with lesions on the lower limbs had a lower rate of cure than patients with upper limbs lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite factors are also known to influence the pathogenesis of leishmaniasis. As L. (V.) braziliensis is polymorphic, dissimilarity among strains at locus CHR 28/425451 or CHR 32/1356278 has been associated with different clinical forms of disease, as well as failure to antimonial therapy (Queiroz et al, 2012;Guimaraes et al, 2016;Silva et al, 2018). Supporting the notion that differences among same-species of leishmania may influence immune response, SLA prepared using L. (V.) braziliensis isolates from DL patients was found to induce higher TNF production in mononuclear cells from both CL and DL patients than SLA similarly prepared using isolates of L. (V.) braziliensis obtained from CL patients (Leopoldo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for the intralesional therapeutic modality, one of the main difficulties for comparing different studies is the lack of standardisation of the procedure, not only for the therapeutic regimen but the technique itself. Facing the few detailed descriptions available for the technique in the literature, we recently published a standardisation of the intralesional infiltration procedure and its validation, the protocol that was followed in this study 8 . Even so, one of the issues still to be defined is the best dosing schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention - The experimental therapeutic intervention consisted of weekly (7 ± 3 days) intralesional infiltration of MA following a previously validated standardised technique 8 ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%